2021
DOI: 10.1007/s00404-021-06197-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between omentin-1 and indices of glucose metabolism in early pregnancy: a pilot study

Abstract: Purpose: Omentin-1 plays an important role in regulating insulin sensitivity outside pregnancy. We aimed to evaluate whether circulating maternal omentin-1 concentrations are associated with fasting serum glucose, insulin, HOMA-IR and maternal obesity as measured by body mass index (BMI) and subcutaneous and intra-abdominal fat thickness measurements in normoglycemic pregnant participants. Methods: Omentin-1 was measured in a sub-cohort of 50 participants in the Omega study. We examined the cross-sectional ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…This conclusion was consistent with the findings of two meta-analyses [40,104]. In a cohort study, Papatheodorou et al, reported a negative correlation between omentin-1 in maternal serum and insulin; however, this association was significant only between non-overweight/obese subjects and not between overweight/obese subjects [105]. A systematic review proposed omentin-1 to be useful in predicting cardiovascular injuries associated with GDM [106].…”
Section: Omentin-1 In Gdm and Pesupporting
confidence: 81%
“…This conclusion was consistent with the findings of two meta-analyses [40,104]. In a cohort study, Papatheodorou et al, reported a negative correlation between omentin-1 in maternal serum and insulin; however, this association was significant only between non-overweight/obese subjects and not between overweight/obese subjects [105]. A systematic review proposed omentin-1 to be useful in predicting cardiovascular injuries associated with GDM [106].…”
Section: Omentin-1 In Gdm and Pesupporting
confidence: 81%